Development of a Malaysian Family Functioning Scale (MFFS) - Sumari, Melati; Md Khalid, Norfaezah; Zulnaidi, Hutkemri; Ibrahim, Nor Hasniah; Ahmed Tharbe, Ida Hartina; Dini Farhana Baharudin (Routledge Journals, Taylor & Francis Ltd, 2024)
Indexed by WOS/ Scopus